Chinese international students’ perceptions of their language issues in U.S. universities: A comparative study - Jiang, Xuan; Yang, Xiuyuan; Zhou, Yuyang (Journal of Interdisciplinary Studies in Education, 2017)
Many students from China in U.S. universities have revealed their difficulties in using English in both communicative and academic contexts. Their difficulties have been a concern in the fields of academic practices and research studies. Accordingly, the current study was developed, to understand and support Chinese students in the U.S. universities. It compared two unpublished exploratory case studies conducted in two universities, which investigated difficulties faced by Chinese students via interviews. Through multi-faceted analysis of participants’ perceptions of their language issues, we argue that English for Academic Purposes (EAP) courses or similar language courses should be more geared to academic writing and speaking for Chinese newcomers. The findings provide insights for reforming the curriculum of language courses in U.S. universities.